A miniaturized bandpass filter implemented with substrate integrated coaxial line. Issue 1 (20th November 2012) - Chu, Peng; Hong, Wei; Wu, Ke; Chen, Jixin; Tang, Hongjun
Abstract This article proposed a miniaturized bandpass filter implemented with the substrate integrated coaxial line (SICL).A four‐pole quasi‐elliptic SICL bandpass filter with two symmetric transmission zeros is designed, fabricated, and measured with a minimal size of 0.168 λ0 by 0.088 λ0, where λ0 is the wavelength of free space at the central operating frequency. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:131–133, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27249